IMPROVING THE MECHANISM FOR ASSESSING THE EFFICIENCY OF HOTEL MANAGEMENT - Berdiyev Jasur Koldoshevich (Ecominds Press, 2025)
The article describes the results of the study on improving the mechanisms for assessing the effectiveness of hotel farms. Analysis of regulatory documents related to tourism and hotel activities has been carried out. A statistical analysis of hotels in the Republic of Uzbekistan and the Kashkadarya region is presented. Conclusions and proposals have been developed to improve the mechanisms for assessing the effectiveness of hotel farms.
Keywords: Hotel, service, mechanism, efficiency, economy, tourism, farm, placement, guest, tourist.